Penerapan Linear Programming untuk Mengoptimalkan Jumlah Produksi dalam Memperoleh Keuntungan Maksimal pada CV Cipta Unggul Pratama - Sugiarto Christian (Bina Nusantara University, 2013)
The purpose of this study is to investigate and understand the barriers and optimize the combination of products in production quantities to gain maximum profit in CV Cipta Unggul Pratama. This study used quantitative approach with survey to collect data. Analysis used forecasting and linear programming method. This analysis was used to combine the right amount of products to get maximum benefit of CV Cipta Unggul Pratama. The results achieved in this research is to know the company in the form of barriers to raw material shortages of 875 m2, labor hours by 4,368 hours, demand forecasting as many as 230 pairs of school shoes, 344 pairs of sports shoes, 450 pairs of shoes and formal employment. The company also had to produce 230 pairs of school shoes, 344 pairs of sports shoes, 450 pairs of shoes and formal employment. Based on the results obtained, research suggested CV Cipta Unggul Pratama makes plans to increase production and to improve the company needs to expand its production or marketing of products territorial expansion.